Oficina pedagógica de escrita para surdos usuários da Libras - Cardoso Junior, Waldemar dos Santos (2018)
This thesis is situated in the research domain named Reading, Writing and Teaching of Portuguese Language, of the Postgraduate Studies in Portuguese Language Program of the São Paulo Catholic University (PUC-SP). The research theme is the pedagogical work of writing a poster, which was developed by deaf learners at the University Extension Project - Portuguese Reading and Writing Workshop for the Deaf (PEU-OLEPS), that takes place at the Pará Federal University (UFPA). The main objective is to develop writing activities for deaf learners create a poster in the context of Portuguese as a second language. The specific objectives are: 1) to verify the knowledge of the deaf learners through diagnostic evaluation of reading and writing; 2) to think about the implications of a pedagogical purpose of writing considering Portuguese as a second language for deaf learners; 3) to describe the processes and stages of the teaching-learning of Portuguese as a second language for deaf learners, based on the pedagogical work with the textual genre named poster. This research, that is qualitative and participant, involved seven deaf learners who use the Brazilian Sign Language. From March to May 2015, these students carried out writing activities of the textual genre named poster. The progress of the activities occurred in three phases: first phase - diagnostic evaluation of the learners related to the reading and writing of textual genres; second phase - pedagogical proposal of writing the textual genre named poster; third phase - writing practice of a poster about the corruption in Brazil. The results indicate that, although the learners initially demonstrated difficulties in textual and written comprehension, the pedagogical work that involved the contextualization of the theme, as well as the textual genre, besides the continuous exercise of writing and rewriting, led the learners to produce texts more meaningful from a communicative point of view